2007
DOI: 10.1080/10410230701283355
|View full text |Cite
|
Sign up to set email alerts
|

Reservations of the Spirit: The Development of a Culturally Sensitive Spiritual Beliefs Scale About Organ Donation

Abstract: This study investigated whether spiritual beliefs offered any explanation for why participants from Korea (N = 146), Japan (N = 134), and the United States (N = 146) were willing or reluctant to register as organ donors. A culturally appropriate measure of spiritual beliefs about organ donation, the Spiritual Beliefs Scale, was developed consisting of 2 factors: (a) Spiritual Connection and (b) Spiritual Concern. Spiritual Connection was a significant predictor of behavioral intention to become an organ donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 51 publications
2
23
2
Order By: Relevance
“…This was similarly identified among other studies of perioperative nurses where willingness to donate organs has been explored 6,29 . However, this view was not compatible with other earlier studies where other health professionals revealed lower levels of commitment towards donating their own organs for a variety of reasons 5,20,24,29 . Individual attitudes and beliefs towards organ and tissue donation were impacted by religious beliefs and religion is an important precursor to how health professionals view OTD.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…This was similarly identified among other studies of perioperative nurses where willingness to donate organs has been explored 6,29 . However, this view was not compatible with other earlier studies where other health professionals revealed lower levels of commitment towards donating their own organs for a variety of reasons 5,20,24,29 . Individual attitudes and beliefs towards organ and tissue donation were impacted by religious beliefs and religion is an important precursor to how health professionals view OTD.…”
Section: Discussioncontrasting
confidence: 96%
“…A common issue identified is emotional and conflicting attitudes and beliefs towards certain aspects of the donation process 1,3,6,12,[13][14][15] . Many health professionals identified varied attitudes and beliefs towards ethical issues, aspects of premortem care from both adult and paediatric donors [16][17][18] and cultural or spiritual beliefs related to having a whole body at the time of death 14,19,20 . Other literature describes the attitudes of health professionals caring for potential organ donors and their professional roles of advocating for the donation process in order to boost organ donation rates 9-11, 15,21-25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural equivalence reflects the minimization of cultural bias and measurement error in the development and/or adaptation of assessment tools . First, we drew from a pool of 63 questions from the three instruments: the Organ Donation & Transplantation Knowledge Survey (ODTK), the Organ Donation Attitude Survey (ODAS), and the Spiritual Beliefs Scale About Organ Donation (SBS) . The ODTK is an 18‐item questionnaire measuring knowledge‐based questions pertaining to organ donation and transplantation issues.…”
Section: Methodsmentioning
confidence: 99%
“…42 First, we drew from a pool of 63 questions from the three instruments: the Organ Donation & Transplantation Knowledge Survey (ODTK), 21 the Organ Donation Attitude Survey (ODAS), 43 and the Spiritual Beliefs Scale About Organ Donation (SBS). 44 The ODTK is an 18-item questionnaire measuring knowledge-based questions pertaining to organ donation and transplantation issues. Respondents are asked to rate their responses using a 4-point scale: "strongly agree" (4 points), "agree" (3 points), "disagree" (2 points), and "strongly disagree" in the recipient of donated organs.…”
Section: Questionnaire Design and Testingmentioning
confidence: 99%